2020
DOI: 10.1038/s41598-020-71822-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time and temperature during melanging on the volatile profile of dark chocolate

Abstract: Chocolate made from small-batch production is known for distinct sensory properties that differentiate its products from large-scale production. Specifically, small-batch processing includes a melanging step, a chocolate refining (a process involving time and temperature to refine texture and flavor) process that occurs in a stone wet-grinder. Chocolatiers understand that melanging is essential to flavor and overall quality, however the influence of melanging on the aroma chemistry of the finished chocolate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…As a result, conching shifts their balance and rearranges the combinatorial code of chocolate's retronasal aroma. Although more severe time and temperature combinations facilitate the removal of volatile fatty acids with disagreeable odor, they can also harm delicate and nuanced flavors, such as fruity and floral notes, associated with low‐boiling alcohols, esters, ketones, and other chemicals, especially in longer conching cycles (above 6–8 h) (Clark et al., 2020; Owusu et al., 2012; Tran et al., 2016). This trade‐off should be considered by manufacturers when sourcing raw materials and setting conching parameters in order to achieve expected flavors, especially in premium chocolates with high cocoa content.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, conching shifts their balance and rearranges the combinatorial code of chocolate's retronasal aroma. Although more severe time and temperature combinations facilitate the removal of volatile fatty acids with disagreeable odor, they can also harm delicate and nuanced flavors, such as fruity and floral notes, associated with low‐boiling alcohols, esters, ketones, and other chemicals, especially in longer conching cycles (above 6–8 h) (Clark et al., 2020; Owusu et al., 2012; Tran et al., 2016). This trade‐off should be considered by manufacturers when sourcing raw materials and setting conching parameters in order to achieve expected flavors, especially in premium chocolates with high cocoa content.…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al focused on the melting process in chocolate production, and revealed variation of chocolate components, especially aroma components, under various conditions by metabolomic analysis using GC-MS (22). The study reported that the aroma components of chocolate change in a time-dependent manner during melting and that the variability of the components differs depending on the volatility of the compounds.…”
Section: Cooking Metabolomicsmentioning
confidence: 99%
“…Chocolate taste and aroma is directly connected to the contents of volatile aroma compounds [52]. Such VC as alcohols, sulfides, and ketones may have a significant impact on chocolate taste and odor [53]. It has been reported that the presence of acetic acid, 2-methylpropanoic acid, 3-methylbutanoic acid and hexanoic acid was observed in dark chocolate [54].…”
Section: Volatile Compounds Profile Of the Dark Chocolatementioning
confidence: 99%